Influence of enterprise risk management framework implementation and board equity ownership on firm performance in Nigerian financial sector: An initial finding - Ahmed, Idris; Ab. Wahab, Norlida (2016)
This study has investigated the influence of ERM framework implementation and Board Equitym Ownership on the performance of financial intuitions in Nigeria. One hundred and sixty three institutions constitute the sample of the study. We collected the data from chief risk officers, chief financial officers and other top level managers of the sampled organisations.The study utilized PLS-SEM path modelling with the help of SmartPLS 2.0 software to test the research framework.The results of the analysis indicated that ERM framework implementation and board equity ownership have a significant positive effects on the financial and non-financial performance of financial institutions in Nigeria.The study recommended the need for business firms to deploy more resources to ensure efficient operations of ERM initiatives in their organisations.Regulatory agencies need to ensure full implementation of ERM across all financial institutions regardless of the size of the firm to actualize its full benefits.The implication of the findings is that financial institutions and other regulatory agencies need to focus on both financial and non-financial performance indicators in their risk management policy..